A Rank Order of Accurate Use at the Syntax-Pragmatics Interface: Evidence from French and Spanish L2 Acquisition - Work, Nicola (Linguistik Online, 2011)
In an attempt to investigate the vulnerability of the syntax-pragmatics interface and to shed light on the acquisition of subjects and objects in two different languages, namely the [+null subject] language Spanish and the [-null subject] language French, this article presents evi-dence from a crossectional and crosslinguistic university classroom study. The experiment in-vestigated various linguistic structures whose use is determined by information structure: pre-verbal subjects, null subjects, postverbal subjects and in situ objects with preverbal subjects, in situ objects with null subjects, Clitic Left Dislocations (CLLD) with null and with postverbal subjects in Spanish; subject clitics, subject dislocations, c’est clefts and in situ objects with subject clitics, in situ objects with subject dislocations, CLLDs with subject clefts and with subject dislocations in French. 76 English learners of French, 67 English learners of Spanish as well as 5 native French controls and 8 native Spanish controls participated in the study. Re-sults of the rating task evaluating learners’ pragmatic intuitions indicate a crosslinguistic rank order of acquisition.